Relações dialógicas das vozes apresentadas pela Campanha da Fraternidade 2022 fala com sabedoria, ensina com amor : um estudo discursivo - Dobrovosk, Lorraine Ramos (2024)
Research in the linguistic field, precisely in the analysis of religious discourse, has greater prominence in academic studies. This is the line in which this dissertation also falls. The central objective is to describe and analyze the dialogical relationships of the voices presented in the base text of the Fraternity Campaign 2022 (CF-2022), in light of Bakhtin's dialogical theory, with the intention of contributing to the formation and construction of an educational reality that promotes the culture of encounter. The CF is an action, promoted annually by the National Conference of Brazilian Bishops (CNBB) and its scope is to elucidate some topic of reflection at a social and cultural level. In 2022, the topic of education was addressed in a post-pandemic context. We found that this text base is very relevant, as it opens up humanistic perspectives for the panorama of education today and considers different voices and social spheres in the construction of its discourse. In this sense, it is in line with the dialogical thought of Bakhtin (1895-1975) and the Circle, 20th century language thinkers, who help us reflect on dialogical relationships in discourse analysis. We present the relationship between such voices, in the light of Bakhtinian theory, especially based on the categories of dialogical relationships, responsible and responsive subject and chronotope. Through a documentary investigation of a qualitative and interpretative nature, we selected as a corpus the central document of the Campaign, which has as its theme: ―Fraternity and Education: Speak with wisdom, teach with love‖. Throughout the research, in addition to presenting the Bakhtinian categories important for the study, we describe the voices of the document from the spheres of: family, school, religion and society, and we try to relate the voices of CF-2022 with Bakhtin's theory and the Circle. The research results point to an educational path based on the conception of an education for dialogue and the promotion of the culture of beauty, good and truth. We consider that this research contributes to linguistic studies, as it reflects dialogical relationships in a panorama as fundamental as education in Brazilian society based on a religious discourse of profound relevance such as that of the Fraternity Campaign.